Aortic valve replacement using interrupted pledgeted non everting suture technique versus simple suture technique in small aortic annulus, does it influence patient prosthetic mismatch - Kothari, Ankur; Jadhav, Uday E. (International Surgery Journal, 2023)
Background: This study aims at comparing post-op outcome and incidence of patient prosthetic mismatch (PPM) post aortic valve replacement (AVR) using pledgeted versus simple suture technique in isolated aortic stenosis patients with small aortic annulus undergoing AVR with 18-21 mm mechanical bi-leaflet valve in Indian population. Methods: A retrospective study, conducted in KEM Hospital, Mumbai in patients who underwent AVR between January 2015 to December 2018. Pre-operative data and 1-year post-op hemodynamic data of patients undergoing AVR using interrupted non everting pledgeted and interrupted simple suture technique were compared. Results: 68 patients were selected for study after applying exclusion criteria (pledgeted 44, simple 24). Both groups were comparable in terms of age (p=0.46), sex (p=0.41), and valve pathologies. Incidence of severe PPM was higher in pledgeted group in patients with valve size 18-19 mm (p=0.20) but similar in valve size 20-21 mm group (p=0.30). Patients with severe and moderate PPM had poor post-operative LV function. Conclusions: PPM is a common and alterable entity. Severe PPM is responsible for adverse hemodynamic function and congestive heart failure among patients with small sized aortic valve implantation (18-21 mm). Use of simple suture technique had a slight benefit over pledgeted technique in reducing incidence of severe PPM (not statistically significant) and better recuperation during short term follow up.